2021
DOI: 10.21203/rs.3.rs-48119/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electronic Reporting of Integrated Disease Surveillance and Response: Lessons learned from Northeast, Nigeria, 2019.

Abstract: Background: Electronic reporting of integrated disease surveillance and response (eIDSR) was implemented in Adamawa and Yobe states, North-East of Nigeria, as an innovative strategy to improve disease reporting. Its objectives were to improve the timeliness and completeness of IDSR reporting by health facilities, prompt identification of public health events, timely information sharing, and public health action. We evaluated the project to determine whether it met its set objectives.Method: We conducted a cros… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…There was significant association between the availability of rumor register and the effectiveness of the IDSR system. There was availability of rumor registers and IDSR technical guidelines in most of the health facilities which is consistent with other studies in Nigeria and Sierra Leone [12], [13] respectively where it was observed that IDSR technical guidelines, consulting room registers, rumor log book, data collection tools and case definitions were available in most of their health facilities. On the contrary, findings from a study in India indicated that there were no rumor log books for documenting rumors in all the health facilities [14].…”
Section: Discussionsupporting
confidence: 88%
“…There was significant association between the availability of rumor register and the effectiveness of the IDSR system. There was availability of rumor registers and IDSR technical guidelines in most of the health facilities which is consistent with other studies in Nigeria and Sierra Leone [12], [13] respectively where it was observed that IDSR technical guidelines, consulting room registers, rumor log book, data collection tools and case definitions were available in most of their health facilities. On the contrary, findings from a study in India indicated that there were no rumor log books for documenting rumors in all the health facilities [14].…”
Section: Discussionsupporting
confidence: 88%